2002
DOI: 10.1007/s00107-002-0296-y
|View full text |Cite
|
Sign up to set email alerts
|

Veneer stiffness predicted by NIR spectroscopy calibrated using mini-LVL test panels

Abstract: Near infrared spectroscopy has been used to predict the stiffness of radiata pine (Pinus radiata D. Don) veneers. Spectral data obtained from 1.2·2.4 m veneer sheets was corellated against stiffness data obtained from 6-ply mini-LVL panels prepared from the sheet. This paper describes the method used to prepare the mini-LVL test pieces and the results of multivariate regression of NIR spectra with the test piece stiffness. The results show the potential for using NIR spectroscopy for on-line assessment of vene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 4 publications
0
27
0
Order By: Relevance
“…Near infrared (NIR) spectroscopy, as a nondestructive detection and identification technology developed over the past 20 years, has the potential to meet these requirements. NIR spectroscopy has been widely used for the evaluation of wood density (Stirling et al 2007), wood grainangle (Gindl and Teischinger 2002), wood chemical composition (Zahri et al 2008), and veneer MOE (Meder et al 2002). It has also been applied in the detection of wood defects, such as discriminating blue-stained wood (Via et al 2006;Via et al 2008), distinguishing the type of fungal decay (Fackler et al 2007;Yang et al 2008), and detecting compression wood (Meder and Meglen 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Near infrared (NIR) spectroscopy, as a nondestructive detection and identification technology developed over the past 20 years, has the potential to meet these requirements. NIR spectroscopy has been widely used for the evaluation of wood density (Stirling et al 2007), wood grainangle (Gindl and Teischinger 2002), wood chemical composition (Zahri et al 2008), and veneer MOE (Meder et al 2002). It has also been applied in the detection of wood defects, such as discriminating blue-stained wood (Via et al 2006;Via et al 2008), distinguishing the type of fungal decay (Fackler et al 2007;Yang et al 2008), and detecting compression wood (Meder and Meglen 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Based on this principle, ultrasonic methods have been advanced as one way to detect knots (Kodama and Akishika 1993;Kabir et al 2003). Additional work has been performed using nondestructive knot identification techniques, such as acoustic waves (Wang et al 2003), Xrays (Cristhian et al 2008), laser scattering based on tracheid effects (Törmänen and Mäkynen 2009), and near infrared (NIR) spectroscopy for wood stiffness (Meder et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…It has long been recognized that heat leads to a partial degradation of cell-wall material that will have an effect on wood chemical composition and mechanical properties (Sanchez-Zapata et al 2011). Such changes in the wood chemical composition lead to veneer coloration changes (that can be monitored using 400 nm to 900 nm spectral data), and to NIR spectra changes (Meder et al 2002, Gaintantzopoulou et al 2009). PLS prediction models for CIE L*a*b* colour space variables were built using the reflectance data acquired in the 400 nm to 900 nm (Fig.…”
Section: Results and Discussion Moisture Content (Mc)mentioning
confidence: 99%
“…However, a significant CIE b* colour space parameter (R 2 = 0.10) was obtained in the range 400 nm to 900 nm, which confirmed that the surface inactivation due to high temperature exposure induces veneer coloration changes that can be monitored using 400 nm to 900 nm spectral data. Coloration changes are caused by chemistry changes related to the disruption of hydrogen bonding and structural damages produced by the heating treatment (Meder et al 2002, Gaintantzopoulou et al 2009). For personal use only.…”
Section: Results and Discussion Moisture Content (Mc)mentioning
confidence: 99%
See 1 more Smart Citation